Increasing student engagement and retention using classroom technologies classroom response systems and mediated discourse technologies - Wankel, Charles; Blessinger, Patrick (Emerald, 2013)
This volume will examine new research on how classroom response systems are being used in higher education to increase learner engagement in an epoch of increasing globalization and diversity. These enabling technologies are reshaping and reframing the practice of teaching and learning in higher education. Through case studies, surveys, and literature reviews, this volume will examine how classroom response systems are being used to improve teamwork and leadership skills in students, to create engaging communities of practice, and how these technologies are being used to create inter-cultural and global experiences. This volume will also discuss a framework for deploying and assessing these technologies.
Includes indexes.
Keywords: Education -- Computers & Technology.; Education -- Classroom Management.; Education -- Higher.; Educational equipment & technology, computer-aided learning (CAL); Education.; Internet in higher education.; Online social networks.; elektronické knihy; electronic books